Community participation during two mass anti-malarial administrations in Cambodia: lessons from a joint workshop - Peto, T; Debackere, M; Etienne, W; Vernaeve, L; Tripura, R; Falq, G; Davoeung, C; Nguon, C; Rekol, H; von Seidlein, L; Dondorp, A; Nou, S; et al. (BioMed Central, 2018)
Two mass drug administrations (MDA) against falciparum malaria were conducted in 2015–16, one as operational research in northern Cambodia, and the other as a clinical trial in western Cambodia. During an April 2017 workshop in Phnom Penh the field teams from Médecins Sans Frontières and the Mahidol-Oxford Tropical Medicine Research Unit discussed lessons for future MDAs.